Nonalcoholic fatty liver disease: opinions, population served, and management from a sample of French hepato(gastroentero)logists (PERSEPT study). Issue 7 (29th March 2022) - Pariente, Alexandre; Rosa, Isabelle; Dharancy, Sébastien; Hanslik, Bertrand; ,
Abstract : Objective: The three-fold objective of this study was to describe the opinions, the population served, and tools used for the management of nonalcoholic fatty liver disease (NAFLD) by French hepato(gastro)enterologists (HGEs). Methods: Seventy-five French HGEs working in hospitals or in private practice, who regularly managed patients with NAFLD, completed three questionnaires: one about their opinions about disease management, one on the 10 first patients with NAFLD they saw in February 2020, and the third about the first five patients meeting the 2016 European Association for the Study of the Liver criteria for specialist referral. Results: Management of NAFLD was seen as challenging, complex, time-consuming, and frustrating. Available treatments were considered to be unsatisfactory by most participants. In the whole population studied (671 patients), 41% were obese, 50% overweight, 49% had type 2 diabetes, 61% dyslipidemia, 51% arterial hypertension, 57% nonalcoholic steato-hepatitis (NASH), 37% advanced fibrosis, and 19% cirrhosis. In the subgroup of 313 patients needing specialist referral, the use of liver biopsy was low (30%) and decreasing, whereas vibration-controlled transient elastometry was high (66%) and increasing; blood fibrosis tests were rarely used. NASH was usually diagnosed without liver biopsy. Nutritional counseling was provided to 3/4 patients, physical activity counseling in 1/5. A personalized therapeutic project was defined in less than one-third of patients. Ursodeoxycholic acid and vitamin E were used in a minority of patients. Conclusion: The management of NAFLD is not considered satisfactory by French HGE who care for a relatively severe population. Noninvasive assessment of fibrosis and multidisciplinary management should be improved.